2020
DOI: 10.3390/children7100178
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Children’s Physical Activity Patterns across the School Year: A Mixed-Methods Longitudinal Case Study

Abstract: Despite the breadth of health benefits associated with regular physical activity (PA), many children in the UK are not sufficiently active enough to meet health guidelines, and tend to become less active as they mature into and throughout adolescence. Research has indicated that children’s school, home and neighbourhood environments can all significantly influence their opportunities to engage in moderate-to-vigorous physical activity (MVPA). However, less is known about how children’s MVPA patterns within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Our results show strong levels of tracking for EE, VPA, and MVPA over a 1-year interval for school-aged boys and girls participating in self-paced games in a GAP format. Therefore, our play-based results open up the need to consider the benefits of tracking children's PA in settings that will encourage and engage children in positive PA behaviors rather than restrict observations to habitual activity (Moghaddaszadeh et al, 2016 ; Truelove et al, 2017 ; Khawaja et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results show strong levels of tracking for EE, VPA, and MVPA over a 1-year interval for school-aged boys and girls participating in self-paced games in a GAP format. Therefore, our play-based results open up the need to consider the benefits of tracking children's PA in settings that will encourage and engage children in positive PA behaviors rather than restrict observations to habitual activity (Moghaddaszadeh et al, 2016 ; Truelove et al, 2017 ; Khawaja et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have assessed tracking statistics over several days/hours during habitual PA and/or organized sports participation with a few studies using a play-based approach. Furthermore, the variations in tracking statistics reported in previous PA studies have used a variety of age groups, tracking intervals, methods, and measurement tools (Jago et al, 2017 ; Khawaja et al, 2020 ). It has been suggested that attention must be given to PA settings/approaches when comparing tracking statistics to assess children's PA behaviors (Malina, 1996 , 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations